Value of preoperative ultrasound-guided fine-needle aspiration for localization in Tc-99m MIBI-negative primary hyperparathyroidism patients. Issue 49 (December 2017) - Li, Wenbo; Zhu, Qingli; Lai, Xingjian; Sun, Jian; Jiang, Yuxin; Ren, Xinyu; Zhang, Qing; Meng, Zhilan; Li, Jianchu; Dai, Qing
Abstract : Abstract: To evaluate the value of preoperative ultrasound-guided fine-needle aspiration (UG-FNA) of ultrasound-detected suspicious parathyroid nodules for localization in Tc-99m MIBI-negative primary hyperparathyroidism patients. From May 2008 to December 2016, Tc-99m MIBI-negative primary hyperparathyroidism patients with ultrasound-detected suspicious cervical nodules underwent UG-FNA. The sample obtained from the solid component of the nodule was subjected to cytological evaluation and immunohistochemical staining. The sample obtained from the cystic component of the nodule or solid nodules was subjected to parathyroid hormone determination. After aspiration, the nodules underwent surgical resection or follow-up. Fifteen nodules (5 cystic, 5 cystic and solid, and 5 solid) from 15 patients were subjected to UG-FNA. Aspirate samples were obtained from 12 of the nodules, and the parathyroid hormone (PTH) levels of these samples were markedly elevated (range: 302– >2500 pg/mL). The samples obtained from the solid components of the 4 cystic and solid and 4 solid nodules were subjected to cytological evaluation, and parathyroid cells were identified in 5 of them. Of these 5 cases, 4 were subjected to immunohistochemical staining, which revealed PTH positivity in the cell block. The UG-FNA results suggested that the suspicious nodules were all parathyroid lesions. The surgical pathology results of 13 cases confirmed the UG-FNA results; the follow-up of 2 cases did not reveal any significant change. The cytological evaluation, immunohistochemical staining, and aspirate fluid PTH determination of UG-FNA were helpful for preoperative localization in Tc-99m MIBI-negative primary hyperparathyroidism patients with ultrasound-detected suspicious parathyroid nodules and can be applied selectively or in combination. Aspirate sample PTH determination should be preferred for nodules with cystic components. Further prospective study with large population is needed to confirm our conclusions.